2022
DOI: 10.3389/fpsyg.2022.906729
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Mindfulness Training Program on Selected Psychological Indices and Sports Performance of Sub-Elite Squash Athletes

Abstract: Mindfulness Acceptance Commitment (MAC) programs have garnered much support in enhancing sport performance through present-moment focus and non-judgmental thoughts. Expanding on previous studies conducted in collegiate and professional settings, the current study investigates the application of MAC amongst national sub-elite athletes. The study was conducted utilizing a single case A-B design, with a total of six sub-elite Malaysian Squash athletes (2 males, 3 females; Mage = 15 ± 2 years) purposively sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Along the same lines, other studies have observed improvements in burnout [ 59 ], decreased stress and anxiety [ 3 , 37 ], improved mood [ 17 ], as well as higher levels of flow and improved sports performance [ 39 , 60 , 61 , 62 ] following the application of a mindfulness programme in athletes. Recent research suggests a reduction in depressive symptoms and an increase in psychological well-being [ 59 , 63 ] and self-compassion [ 3 ].…”
Section: Discussionmentioning
confidence: 74%
“…Along the same lines, other studies have observed improvements in burnout [ 59 ], decreased stress and anxiety [ 3 , 37 ], improved mood [ 17 ], as well as higher levels of flow and improved sports performance [ 39 , 60 , 61 , 62 ] following the application of a mindfulness programme in athletes. Recent research suggests a reduction in depressive symptoms and an increase in psychological well-being [ 59 , 63 ] and self-compassion [ 3 ].…”
Section: Discussionmentioning
confidence: 74%
“…Internal consistency was good (α = .92). The AAQ-II is also commonly used to examine inflexibility in both college-aged and athletic populations, and shows strong psychometric properties across cultures (Chang et al, 2017;Dehghani et al, 2018;Krafft et al, 2019;Wong et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, by promoting mindfulness, athletes are more likely to engage in self-reflective behavior. Research suggests that Mindful-ness-Acceptance-Commitment (MAC) interventions emphasize acceptance and non-reactivity, enabling individuals to cope with stress without being overwhelmed ( Wong et al, 2022 ). Athletes frequently encounter high-pressure situations and substantial physical and mental challenges, from which they can benefit by cultivating this calmness.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%